ANALISIS PENGARUH FINTECH ADOPTION TERHADAP PROFITABILITAS BANK UMUM KONVENSIONAL DI INDONESIA - Fuadi, Ahmad Melky; Munawar, Munawar (Contemporary Studies in Economic, Finance and Banking, 2022)
Covid-19 pandemic that occurred in Indonesia had a serious impact on all sectors, one of which was the financial and banking sectors. This phenomenon requires the banking sector to overcome it through the application of financial technology. This study aims to determine the effect of Fintech adoption on the financial performance of conventional commercial banks in Indonesia in terms of the Return on Assets ratio during the period 2013 - 2021. This study uses the Error Correction Term analysis method to see the effect of the independent variable on the dependent variable in the long term. short and long term. The independent variables in this study include mobile banking, internet banking, and phone banking and the dependent variable is the ratio of ROA. In addition, this study includes control variables consisting of bank size and total credit as well as a dummy variable, namely the covid-19 pandemic. This study results that mobile banking has a positive and significant effect on ROA in the short and long term, internet banking has a negative effect. and significant to ROA in the short and long term, phone banking has a positive but not significant effect on ROA in the short and long term.